(untitled) (Pubmet, 2022)
Citizen Science just like many other elements of Open Science has a different understanding in Western Europe than in Central-Eastern Europe (Ex-communist countries). Because of many reasons CS is still least-known though there are more and more background supporting opportunities. The new roles of the libraries are gaining appreciation as we are working with different stakeholders. Citizen Science could be one of the most valued pillar of Open Science if libraries are involved in it as aggregators, hubs, but the libraries must be ready to do so. The presentation is about how and why libraries should be engaged in Citizen Science.